Propaganda of legal knowledge about Kazakhstan citizenship - Turlayev, A.V.; Balgimbekova, G.U. (Bulletin of the Karaganda University “Law Series”, 2024)
In the article problematic issues surrounding the promotion of legal knowledge regarding Kazakhstan citizenship were considered, recognizing citizenship as a fundamental legal institution shaping modern Kazakhstan society’s statehood. The research conducts a comprehensive analysis and synthesis of the theory and practice of disseminating legal knowledge about citizenship, aiming to identify solutions to normative consolidation challenges. Through a combination of general scientific and specialized legal methods, including analysis and theoretical generalization, as well as an examination of legal norms on citizenship, the study identifies the main trends in improving legal knowledge about citizenship. The main research outcome underscores the necessity to enhance legal measures aimed at expanding the use of forms and methods for disseminating legal knowledge about Kazakhstan citizenship. As a result, the article proposes supplementing citizenship legislation with norms mandating government bodies to provide information and advice on citizenship issues. It suggests widening public awareness about the importance of citizenship as a legal institution and supplementing political and legal acts with provisions to increase Kazakhstani society’s awareness of citizenship.